Green New Deals: What Shapes Green and Deal?. Issue 3 (3rd July 2022) - Levidow, Les
ABSTRACT: In the US and UK, Green New Deal (GND) agendas have gained significant support as means to reconcile environmental sustainability with a socially fairer economy. Their transformative vision has stimulated proposals such as more public goods, workers' cooperatives, eco-localisation and caring activities. When seeking support from major political parties, however, GND agendas have undergone pressure to accept decarbonisation technofixes, as promoted by carbon-intensive industries in alliance with their trade unions. Such promises have provided an investment imperative for dubious low-carbon remedies, or an alibi to await their feasibility, or both at once. These agendas imagine the nation as a unitary economic space needing technoscientific advance for a global competitive advantage. Divergences within the labour movement express rival sociotechnical imaginaries of a low-carbon future. This conflictual process has shaped what counts as Green and Deal for a GND. Similar tensions will arise around any low-carbon transition, given the wider capitalist frameworks of Green Keynesianism and Green Growth. To go beyond them will depend on political struggles to disrupt the hegemonic cross-class alliance, to create different alliances and to gain state support for their agendas.